Exploring Caregiver Perspectives of Social and Motor Skills in Children With Autism Spectrum Disorder and the Impact on Participation - Rios, P. Camila; Scharoun Benson, Sara M. (Frontiers in Psychology, 2020)
Participation is a key aspect of quality of life, and is essential for children’s well-being, yet children with disabilities are at risk for lower participation in social activities. For children with Autism Spectrum Disorder (ASD), social skills may present a significant obstacle for participation in activities of daily life; however, motor skill development may also serve an important contributing factor. Nevertheless, the link between social and motor skills in children with ASD is not fully understood. The current research implemented semi-structured interviews to garner descriptive insights from caregivers (N = 17) into the social and motor skills of 5- to 9-year-old children with ASD, and the impact on participation in social activities. A constant comparative method was used to generate a coherent and thematic representation of caregivers’ experiences. Thematic analysis revealed core consistencies in three areas: (1) Caregivers viewed participation differently than their children; (2) Participation levels of children with ASD are context specific; (3) Challenges with social skills were perceived to present a greater obstacle to participation than motor skills. Overall, the notion that ASD is a heterogeneous disorder was made very apparent. Although caregivers believe there to be immense value in current treatment and intervention options, the availability and access to such options was a major barrier. The effectiveness of intervention programming designed to increase participation is contingent on understanding factors that affect participation. Implications concerning caregivers’ perspectives are discussed.